2017
DOI: 10.17705/1cais.04025
|View full text |Cite
|
Sign up to set email alerts
|

Noise or Quality? Cross-Nested Hierarchical Effects of Culture on Online Ratings

Abstract: Abstract:Previous feedback system research in a variety of contexts has focused on the impact that ratings (as proxies for quality) have on a variety of social and economic outcomes with equivocal findings. These mixed findings may be partially due to noise (factors not related to quality) embedded in aggregated or average positive and negative ratings. One significant source of ratings noise may come from culturally diverse raters' issuing ratings in virtual environments. Culture impacts how groups of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 125 publications
(207 reference statements)
0
2
0
Order By: Relevance
“…We used multiple coders to code our data consistent with the prior research (Mattson, 2017;Vaast et al, 2013). We first coded 50 free-form text responses together to develop a consistent process among the different coders.…”
Section: Resultsmentioning
confidence: 99%
“…We used multiple coders to code our data consistent with the prior research (Mattson, 2017;Vaast et al, 2013). We first coded 50 free-form text responses together to develop a consistent process among the different coders.…”
Section: Resultsmentioning
confidence: 99%
“…This is because customers with higher uncertainty avoidance are more risk-averse; therefore, they tend to search for the attributes of the product and service, leading to higher expectations. The cultural distance was also found to be related to a negative review rate (Mattson, 2017;Stamolampros et al, 2019). Because when the cultural distance between customers and sellers is higher, there is a higher chance of cultural gaps and differences, and these differences may translate into consumers' dissatisfaction.…”
Section: Stimulusmentioning
confidence: 96%
“…Existing studies have primarily examined individual, product, platform, or social‐level antecedents of online reviewer behavior. At individual level, prior research shows that user characteristics such as gender, age and cultural background can affect their online review behaviors (e.g., Hong et al, 2016; Mattson, 2017). For example, Hong et al (2016) found that customers from collectivist cultures were unlikely to give a rating that significantly differed from the average prior rating.…”
Section: Literature Reviewmentioning
confidence: 99%